Anticancer potential of Carica papaya Linn black seed extract against human colon cancer cell line: in vitro study - Nadia S. Mahrous; Enas A. Noseer (BMC, 2023)
Abstract Background Since cancer is one of the most prevalent diseases in the world, further studies are needed to identify the effective therapeutic modalities. The second deadliest and third most common cancer is colorectal cancer (CRC). Papaya (Carica papaya Linn) seeds offer anti-cancer properties that can cure various types of cancer, such as liver and prostate cancer. Methods The study aimed to evaluate the anti-cancer activity of Carica papaya seed extract on colorectal cancer cell lines (Caco-2) and used techniques to assess the anti-cancer potential. The effectiveness of SE on cell proliferation and the viability of HTB-37 Caco-2 and C-166 cells were assessed using the MTT test. Real-time RT-PCR was used to measure gene expression levels and evaluate the activity of genes involved in apoptosis, including caspase-3, p53, Cycs, and Bcl-2. Finally, flow cytometry was used to analyze apoptosis induction by detecting changes in cell morphology and DNA content. Results The study showed that the MTT reduction assay was dependent on cancer cell type and concentration of SE compared to the control cells and C-166, with a mean IC50 value of 9.734 ug/ml. The cytotoxicity was accompanied by some morphological alterations in the colorectal cancer cell line (Caco-2). The expression of the genes for p53, Cycs, and caspase-3 was substantially up-regulated, while Bcl-2 was dramatically down-regulated compared to control cells. The cell cycle arrested at the G2-M phase and the presence of early and late apoptotic characteristics post-treatment increased the apoptotic profile. Conclusion It concluded that papaya seeds aqueous extract could act as a novel therapeutic option for colorectal cancer (CRC).